Dragon fruit peel pectin: Microwave-assisted extraction and fuzzy assessment - Tongkham, Nudthapong; Juntasalay, Boonyawee; Lasunon, Patareeya; Sengkhamparn, Nipaporn (Agriculture and Natural Resources, 2017)
Dragon fruit peels were used as a material for pectin extraction. Microwave-assisted extraction (MAE) using powers of 300, 450 or 600 Wand heating times of 5 or 10 min were investigated. Compared to the conventional method, the MAE method produced a higher yield of pectin, with the highest pectin yield (23.11%) being obtained using a microwave power of 600 W and a heating time of 10 min. However, during the MAE extraction, the degradation of pectin may have occurred which resulted in a drop in viscosity. The fuzzy assessment method (FAM) was applied to determine suitable conditions for MAE. The highest overall performance index obtained from FAM indicated that a microwave power of 450 W and an extraction time of 5 min were suitable conditions to produce a high pectin quantity with less degradation. Moreover, the anhydrouronic acid content, degree of esterification and the Fouriertransform infrared spectrum of MAE pectin did not differ from the conventional pectin and therefore, the extract could be categorized as a high methoxyl pectin.